The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5cc03649f
|View full text |Cite
|
Sign up to set email alerts
|

Aza-BODIPY dyes with enhanced hydrophilicity

Abstract: Attempts to make a diamino disulfonic acid derivative of an aza-BODIPY showed it was difficult to add BF2 to a disulfonated azadipyrromethene, and sulfonation of an aza-BODIPY resulted in loss of the BF2 fragment. We conclude the electron-deficient character of aza-BODIPY dyes destabilizes them relative to BODIPY dyes. Consequently, sulfonation of the aza-BODIPY core is not a viable strategy to increase water solubility. This assertion was indirectly supported via stability studies of a BODIPY and an aza-BODIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 15 publications
1
52
0
1
Order By: Relevance
“…Moreover, it can be predicted that after the rational design of the molecular sensor, which means the functionalization of the corresponding fluorophore with an adequate receptor to the target entity or property, BODIPY could be the right choice as the label to visualize the desired molecule or environmental property. Besides, the versatility of this dye makes it feasible to add a further degree of functionalization to enhance its solubility (i.e., in water) or to favor its adsorption or linkage to a specific place of a biomolecule . The use of these kinds of luminescent molecular sensors is very attractive for biochemistry, as will be emphasized in the next section.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can be predicted that after the rational design of the molecular sensor, which means the functionalization of the corresponding fluorophore with an adequate receptor to the target entity or property, BODIPY could be the right choice as the label to visualize the desired molecule or environmental property. Besides, the versatility of this dye makes it feasible to add a further degree of functionalization to enhance its solubility (i.e., in water) or to favor its adsorption or linkage to a specific place of a biomolecule . The use of these kinds of luminescent molecular sensors is very attractive for biochemistry, as will be emphasized in the next section.…”
Section: Discussionmentioning
confidence: 99%
“…This result supported and confirmed that nucleophilic addition of CN – was taken place at the isothiocyanate moieties of the N1 sensor. Additionally, 1 H‐NMR spectra of the N1 at the position of pyrrole (chemical shift 7.06 ppm), with and without CN − did not exhibit a significant shift, which indicated that the binding of CN − did not occur at the pyrrole (Figure ). This evident strongly indicated that the CN − did not react to pyrrole ring of aza BODIPY N1 , otherwise the significant change of 1 H‐NMR spectra must be observed due to the change of conjugated system of the pyrrole ring after nucleophilic addition of CN − .…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of compounds 1–4 : Using the similar procedure from previous work, the title compounds were prepared. The synthetic steps were demonstrated in Scheme …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, interest has been increasing in the 4-bora-3a,4a,8-triazaindacene dyes (commonly referred to as aza-BODIPY dyes) owing to their efficient fluorescence in the far-red and near-IR regions of the spectrum. Aza-BODIPYs are basically BODIPY derivatives with the meso-carbon atom replaced by an imine type nitrogen atom ( Figure 6) (Kamkaew and Burgess, 2015;Ulrich et al, 2008;Wu and O'Shea, 2013).…”
Section: A N U S C R I P Tmentioning
confidence: 99%